2016
DOI: 10.22302/iribb.jur.mp.v79i1.69
|View full text |Cite
|
Sign up to set email alerts
|

Optimasi produksi diasilgliserol dari crude palm oil menggunakan lipase spesifik 1,3-gliserida dari Rhizopus oryzae TP-2 Optimation of diacylglycerol production from crude palm oil using specific lipase of 1,3-glyceride from Rhizopus oryzae TP-2

Abstract: Modern lifestyle caused the increasing prevalence ofobesity that precedes degenerative disease such as coronarycardiovascular disease, hypercholesterolemia, stroke, anddiabetes mellitus. Use of healthy oil in the daily food diet couldreduce the risk of the disease. One of healthy oils that proved tobe useful for human health is diacylglycerol (DAG).Unfortunately, production of DAG in Indonesia is hampered bythe relatively high price of the lipase enzyme. To overcome theprovision of costly imported lipase in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Too much oil as inducer in production media leads to low lipase activity due to low oxygen transfer into medium (Lima et al 2003). Pramitasari et al (2012) used 2% olive oils inducer to produce lipase and Suharyanto et al (2011) used 2% crude palm oil (CPO) to produce 1.3 glyceride specific lipase from Rhizopus oryzae TP-2. Media selection and production period based on the comparison of enzyme specific activity (Fig 11) indicates that the optimum activity period of PDB and olive oil media was at 48 h. In margarine raw material selection and making, POs can be mixed with PKOo which has shorter lipid chain to make the mixture better functional property such spread ability at room temperature (Noor et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Too much oil as inducer in production media leads to low lipase activity due to low oxygen transfer into medium (Lima et al 2003). Pramitasari et al (2012) used 2% olive oils inducer to produce lipase and Suharyanto et al (2011) used 2% crude palm oil (CPO) to produce 1.3 glyceride specific lipase from Rhizopus oryzae TP-2. Media selection and production period based on the comparison of enzyme specific activity (Fig 11) indicates that the optimum activity period of PDB and olive oil media was at 48 h. In margarine raw material selection and making, POs can be mixed with PKOo which has shorter lipid chain to make the mixture better functional property such spread ability at room temperature (Noor et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Test result indicated that the three isolates were capable of producing orange fluorescence and forming clear zone on the media. According to Hou and Johnston (1992), fluorescence zone formed on selection media with CPO as lipid source also indicated that the isolate was capable of producing lipase which break triacylglycerol (TAG) in CPO into DAG, MAG, or FFA, and with Rhodamin B forming fluorescence compounds.Specific lipase hydrolyses ester bond at 1,3 position, producing fatty acid, monoacylglycerole, and diacylglycerole (Suharyanto et al 2011).…”
Section: Uncultured Fungusa1a10711mentioning
confidence: 99%
“…Dengan cara ini, biokonversi enzimatis akan lebih praktis (Garcia et al 2011) dan dapat dilakukan lebih mudah dan murah dibandingkan dengan penggunaan enzim bebas. Amobilisasi enzim telah berhasil dilakukan untuk enzim desaturase dan enzim lipase (Ren et al, 2011;Suharyanto et al, 2011;Tri-Panji et al, 2014). Namun, aktivitas dan stabilitas lipase masih perlu ditingkatkan.…”
Section: Pendahuluanunclassified
“…Gliserolisis dilakukan dengan mereaksikan enzim amobil (hasil amobilisasi dengan zeolit dan serbuk tulang) dengan campuran gliserolisis dengan variasi komposisi: a) 0,8 g gliserol, 40 mL heksana, 50 mL buffer tris-HCl 0,05 M pH 7 dan 2 g CPO (Tri-Panji et al, 2014) dan b) 0,8 g gliserol, 20 mL heksana, 50 mL buffer tris-HCl dan 3 g CPO (Suharyanto et al, 2011). Kemudian campuran diinkubasi pada suhu kamar, pH 7, dengan variasi waktu hingga 18 jam.…”
Section: Optimasi Gliserolisis Cpo Dengan Lipase Amobilunclassified